Fundamental Approaches to Software Engineering
DOI: 10.1007/978-3-540-78743-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Towards Faithful Model Extraction Based on Contexts

Abstract: Abstract. Behaviour models facilitate the analysis of software systems using model-checking tools to detect errors and generate counterexamples. Such models can be generated from existing implementations using a model extraction process. This process should guarantee that an extracted model is a faithful representation of the system, so that analysis results may be trusted. This paper discusses the formal foundations of our model extraction process based on contexts. Contexts are abstractions of concrete state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…6. It describes that a document was opened (lines 1-10), an invalid option was entered (lines [11][12][13][14][15], and then the next input was the command to edit the document (lines [16][17][18][19][20][21][22][23]. Lines 24-33 represent the execution of option print, followed by a document save (lines [34][35][36][37][38][39][40][41][42].…”
Section: Information Gatheringmentioning
confidence: 99%
See 2 more Smart Citations
“…6. It describes that a document was opened (lines 1-10), an invalid option was entered (lines [11][12][13][14][15], and then the next input was the command to edit the document (lines [16][17][18][19][20][21][22][23]. Lines 24-33 represent the execution of option print, followed by a document save (lines [34][35][36][37][38][39][40][41][42].…”
Section: Information Gatheringmentioning
confidence: 99%
“…Contexts have been successfully used to extract models from sequential and concurrent systems [17] and the analyses carried out using our models in a number of case studies [18] have demonstrated that they are correct abstractions of the systems they describe at a certain level of abstraction and according to a set of observed behaviours (traces). Hence, the extracted models are useful for many analysis purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Labelled Transition System Extractor (LTSE) tool [6] extracts, from an annotated Java code, the context information as a table of contexts ( Figure 3) and a set of traces of contexts ( Figure 4), which are used in the method described in [6], to generate models of Labeled Transition Systems (LTS) [8]. Our approach uses the data extracted by the LTSE tool to generate a graph grammar with rules that represent the possible transitions of the program.…”
Section: A Model Extractionmentioning
confidence: 99%
“…In this case models are heavily dependent on parameters that must be provided a-priori by domain experts or extracted by other similar systems. In [11] the formal foundations of model extraction process based on contexts is discussed. The correctness of the models is affected by the set of attributes used as the system state, while in our approach is guaranteed for safety properties.…”
Section: Conclusion and Related Workmentioning
confidence: 99%